The influence of personal finance on the financial management of microenterprises in Rio de Janeiro - Pereira da Silva Catarino, Gabriela (2020)
The study aimed to evaluate the influence of the personal finances of the microentrepreneur on the financial management of its microenterprise. To this end, a survey was carried out with 96 owners of microenterprises located in Rio de Janeiro and who have been operating more than two years under the same management. A questionnaire with closed questions was used in order to fulfill the objective, these were analyzed through the association between the two qualitative variables, competencies in personal finance and financial management capacity, from a quantitative approach. The work becomes relevant as the smaller companies in Brazil represented 92% of the total of private companies. Microenterprises with 2 years old, in particular, present a mortality rate of 45% p.y., in which education and training are considered as factors limiting the opening and maintenance of new businesses. It was possible to notice that there is a relationship between personal financial management and the financial management of microenterprises. Many do not separate personal accounts from company accounts, do not have professional training, many who do not do personal planning do not have / use financial statements. It was also noted that owners with personal debts also have debt in their business and those who do not have personal investments also end up having no investment in their companies. Understanding how microentrepreneurs in Rio de Janeiro deal with the personal x professional financial issue can help to improve new business development programs in different regions.